Study of Morphological and Morphometric Characteristics of Worker Bees Tetragonula clypearis in North Lombok Regency, West Nusa Tenggara Province, Indonesia - Erwan Erwan; Munaris Munaris; Muhammad Muhsinin (Jurnal Biologi Tropis, 2022)
This study aimed to describe the morphometric characteristics of the worker bee Tetragonula clypearis in Salut Village, District Kayangan, North Lombok Regency. The research material used was worker bee Tetragonula clypearis taken from 40 stup in two livestock groups, namely 20 stup in the Harapan Keluarga group and 20 stup in the Tunas Muda group in Salut Village, Kayangan District, North Lombok Regency. Each stup took three samples of worker bees for morphometric analysis (n=120). Morphological characters were observed under a stereo microscope connected to an Optilab camera. The character of T. clypearis is the thorax is black and hairy, and there are six hair bands on the mesoscutum and dark brown tibia. Metasoma has a variety of colours, ranging from pale yellow with black stripes, yellow and black, and pale yellow. The morphometric measurements included body length, head width, wing length, genna width, second flagellomere diameter, and body weight. The results showed that the seven morphometric measurement variables of the worker bee Tetragonula clypearis did not show significant differences (P>0.05) in the two cultivation groups. The value of the diversity coefficient <15% indicates that the morphometrics of the worker bee Tetragonula clypearis is uniform in both cultivation groups in Salut Village, District, Kayangan, North Lombok Regency.